National income statistics for Poland, 1970-1980 - Fallenbuchl, Zbigniew M. (Washington, D.C., U.S.A. : World Bank, 1985)
This paper presents estimates of Gross Domestic Product, Gross National Product, their component and rates of growth which are based on published statistics, Information available in various published sources and assumptions
"A background study for Dollar GNPs of the U.S.S.R. and Eastern Europe"--Cover.
Bibliography: p. 110-115.
osa;15/11/17
Loans
Keywords: Gross national product; National income; Poland